Pengaruh Zat Pengatur Tumbuh Benzyl Amino Purin di dalam Bioreaktor Sistem Perendaman Sesaat Pada Multiplikasi Tunas Pisang Seblot (Musa acuminata L.) - Inah Karlinah; Sulastri Isminingsih; Susiyanti Susiyanti; Nurmayulis Nurmayulis (Jurnal Agroekoteknologi, 2022)
This study aimed to determine the effect of the growth regulator Benzyl amino purine for multiplication of banana shoots seblot in a bioreactor with a momentary immersion system. This research was carried out at the Physiology Biotechnology Laboratory Faculty of Agriculture Sultan Ageng Tirtayasa University, from March to May 2022. The research design was used a Randomized Block Design consisting of one factor, namely the concentration level of 6-Benzyl amino purine which consisted of six levels (0, 0.5, 1, 1.5, 2 and 2.5 ppm). The treatment of growth regulator Benzyl amino purine gave a very significant effect on the parameters of leaf emergence time and number of shoots at 1 and 5 weeks after planting (1.74 shoots). The number of leaves had a significant effect (1.96 sheet). While the parameters of the percentage of live explants, the percentage of rooted explants, the time of emergence of shoots and the percentage of contamination gave no significant effect.